Synthesis and application of cobalt and polyoxomolybdatecontaining alumina systems; Journal of Physics: Conference Series; Vol. 1611 : Prospects of Fundamental Sciences Development (PFSD-2020) - Akimov A. S. (2020, 2020)
Title screen